The organisation of mind - Shallice, Tim.; Cooper, Richard P. (New York : Oxford University Press, 2011)
To understand the mind, we need to draw equally on the fields of cognitive science and neuroscience. But these two fields have very separate intellectual roots, and very different styles. So how can these two be reconciled in order to develop a full understanding of the mind and brain. This is the focus of this book.
Cognitive neuroscience: the seeds are sown -- Why'cognitive' neuroscience? -- Bridging the theoretical gap: from the brain to cognitive theory -- From cognitive impairment to cognitive models -- Inferences to the functional architecture from functional imaging -- On the semantic elements in thought -- Short-term retention, buffers, priming, and working memory -- On operations -- On supervisory processes -- Higher level modulatory processes: episodic memory -- Consciousness -- Thinking.
Includes bibliographical references (p. [505]-571) and index.
Keywords: Cognitive neuroscience; Brain; Thought and thinking